KAJIAN KONSEP EASY MAINTANANCE PADA FASADE ARSITEKTURAL MUSEUM TSUNAMI ACEH MENDUKUNG KEBERLANJUTAN GEDUNG - Rikza, Rikza; Ferah Yosantia, Muhammad (Jurnal Media Teknik Sipil Samudra, 2025)
The Aceh Tsunami Museum is a public building characterized by complex architectural design, both in terms of historical significance and aesthetics. Proper maintenance and upkeep are essential to ensuring the sustainability of its function, aesthetic value, and user safety. This study aims to identify the materials utilized in the museum's construction and categorize them based on the 'Easy Maintenance' concept. A descriptive qualitative approach was employed as the research method, with data gathered through case studies, field observations, and literature reviews. The findings indicate that the use of Glass Reinforced Concrete (GRC), curtain walls, and aluminum offers high durability; however, their maintenance requires specialized equipment. Furthermore, the selection of appropriate materials and the implementation of passive design strategies significantly influence the long-term maintenance and preservation of the building.